PERKEMBANGAN ANGKLUNG TOEL PADA TAHUN 2010-2019 DI SAUNG ANGKLUNG UDJO BANDUNG DITINJAU DARI ASPEK TEKNOLOGI - Rossari, Fransisca Inneke (Jurnal Penelitian Musik, 2020)
This study uses descriptive qualitative methods, with data collection techniques including interviews, literature study and documentation. This research was conducted at Saung Angklung Udjo Bandung. The object of this research is the musical instrument Angklung Toel. The purpose of this study was to determine the process of the development of angklung toel types in 2010-2019 at Saung Angklung Udjo Padasuka, Bandung. The results showed that Angklung toel is the latest creation of conventional angklung in general. There have been four developments of angklung toel types in terms of technology, namely Angklung toel 2010, the second development is Yanklung Toel 2013, the third development is The Great Angklung toel 2015 which is known as the piano angklung toel because its shape is almost similar to the shape of a piano instrument that has a board touch, the fourth development is The Great Yanklung Toel 2016. Angklung toel has been very much in demand by the public in entertainment events, especially in Bandung and is used in learning and the appearance of a work, from schools to tertiary institutions in Bandung.